If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(3-10x)1/3=1
We move all terms to the left:
(3-10x)1/3-(1)=0
We add all the numbers together, and all the variables
(-10x+3)1/3-1=0
We multiply all the terms by the denominator
(-10x+3)1-1*3=0
We add all the numbers together, and all the variables
(-10x+3)1-3=0
We move all terms containing x to the left, all other terms to the right
(-10x+3)1=3
| 5-1=5+x | | -17r+20=-8-19r | | 5-1=5+x+ | | 6+9d=8d | | 7y-3y(y=2 | | -(x-4)+5=-3 | | x+4=60-6x | | 4x+8+6x+(-5)=33 | | 5x-(3x+2)-(1)=0 | | 15-8p6.75=10 | | 3x32=56 | | 8g-8=9+8g= | | 4(3x+5)=52 | | 28-6x=8(-4x-3) | | -10+m=10+7+4m | | 2.4x=3.9-x | | 28-6x=8(4x-3) | | 10x11=121 | | 2y+12.875=45.625 | | 10−2t=20 | | 1+9b=10b+9 | | -5=2x=+11 | | -6w=4w+20 | | 4x+(x-5)=3(2x-4) | | 5x-(3x+2(-(1)=0 | | 8(x-4)-25=2(x+4) | | -3x+15=6(x-8 | | 10+7j=7j | | 9+5r=-6+10r | | 5x-(3x+2(=1 | | 6x+54=162 | | 5(7+4x)-7=48 |